Preparation method of low-cost and easy-to-form flexible magneto-optical composite material
By dispersing magnetic nanoparticles in ZIF-8 and modifying them into a bridge agent in PMMA, a highly transparent flexible magneto-optical composite material is prepared, which solves the problems of long preparation period, high cost and difficult molding of traditional magneto-optical materials, and realizes low-cost and high-performance magneto-optical composite material.
Patent Information
- Application Number
- CN202411715647.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-27
AI Technical Summary
Traditional crystal and glass magneto-optical materials have long preparation cycles, high cost, difficult to form, difficult to make devices of opposite sex, and difficult to achieve small-scale integration of optical components.
Fe3O4 or CoFe2O4 or NiFe2O4 nanoparticles were dispersed in ZIF-8 by co-precipitation method, and modified by PgC5Cu to uniformly disperse them in PMMA, thereby preparing a highly transparent flexible magneto-optical composite material.
It realizes a low-cost, easy-to-form flexible magneto-optical composite material, with high optical transmittance, excellent magnetic and optical properties, and is suitable for optical fiber communication, integrated optical devices and new special-shaped magneto-optical devices.
Smart Images

Figure CN119529458A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flexible magneto-optical composite materials, and in particular relates to a method for preparing a low-cost, easily moldable flexible magneto-optical composite material. Background Art
[0002] In the field of optical information, magneto-optical materials, as a key functional material, have been widely used in the development of various high-performance devices such as modulators, isolators, circulators, magneto-optical switches and sensors due to their unique magneto-optical effects, such as the Faraday rotation effect. These devices play an irreplaceable role in many important fields such as communications, laser technology, military industry and national defense. At present, bismuth-doped rare earth iron garnet (BRIG) crystals have become one of the most widely used magneto-optical materials due to their excellent transmittance and significant Faraday effect in the near-mid-infrared region, promoting the rapid development of technologies such as optical communications, lidar and the Internet of Things. At the same time, in response to the needs of the visible to near-infrared band, researchers have developed magneto-optical crystals such as terbium gallium garnet (TGG), terbium scandium aluminum garnet (TSAG) and terbium potassium fluoride (KTF), providing efficient high-power optical isolation solutions for industrial laser systems. In addition, with the rise of terahertz technology, the research and development of terahertz band magneto-optical crystals such as terbium erbium bismuth rare earth iron garnet (TbErBi:RIG), cerium fluoride (CeF3), holmium ferrite (HoFeO3) and indium antimonide (InSb) have further broadened the application scope of magneto-optical materials and applied them to new generation magneto-optical devices such as terahertz magnetic polarization conversion, magneto-optical sensors / imagers, non-reciprocal phase shifters and isolators. Another indispensable magneto-optical material, magneto-optical glass, such as magneto-optical glass with multiple components such as terbium doped, cerium doped and lead borate, has shown broad application prospects in the fields of magneto-optical waveguides, optical fibers, modulators and optical fiber current sensors with its unique performance advantages.
[0003] Although magneto-optical crystals and glass materials occupy an important position in traditional applications, they still face several core challenges that need to be solved. First, traditional crystal and glass magneto-optical materials often have a long preparation cycle, high energy consumption, and high material preparation costs; second, crystal and glass magneto-optical materials are rigid structures, difficult to shape, and not easy to make heterogeneous devices; more importantly, when designing integrated optical systems, it is difficult to integrate optical components on a very small scale due to the physical properties of traditional crystal materials and processing technology limitations. If the magnetic element particle size is prepared to be small enough and highly uniformly dispersed in a transparent polymer, then there is hope of obtaining highly transparent and strong magneto-optical materials.
[0004] This patent proposes for the first time a low-cost, easy-to-form flexible magneto-optical material, which disperses Fe3O4 or CoFe2O4 or NiFe2O4 with strong magneto-optical effect in ZIF-8, and then uses PgC5Cu metal organic nanocapsules as a bridge between MOF and polymer to achieve uniform dispersion of nanoparticles with strong magneto-optical effect in transparent polymer materials in steps, and prepares a highly transparent flexible magneto-optical composite material, and explores the optical, magnetic and magneto-optical properties of the flexible magneto-optical composite material. This material successfully combines flexibility with significant magneto-optical effect, breaking the rigid constraints of traditional magneto-optical materials, and is expected to be used in the development of low-cost, highly integrated and special-shaped new magneto-optical devices. Summary of the invention
[0005] In view of the problems of long preparation cycle, high cost, difficult molding, difficulty in making heterogeneous devices, and difficulty in optical integration of traditional crystal and glass magneto-optical materials, the present invention provides a low-cost, easy-to-mold flexible inorganic-polymer composite magneto-optical material and its preparation method and application. It adopts a co-precipitation method to disperse Fe3O4 or CoFe2O4 or NiFe2O4 with strong magneto-optical effect in ZIF-8, and then uses PgC5Cu metal organic nanocapsules as a bridge between MOF and polymer to achieve nanoparticles with strong magneto-optical effect uniformly dispersed in transparent polymer materials in steps, and waits for the solvent to evaporate and mold in a specific mold to prepare a highly transparent flexible magneto-optical composite material. The composite material is expected to be practically applied in optical fiber communications, integrated optical devices, miniaturization, and new heterogeneous magneto-optical devices.
[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme: A low-cost, easy-to-form flexible magneto-optical composite material, the molecular formula of the composite material is: AB2O4-ZIF-8@PgC5Cu / PMMA, where A is Fe, Co, Ni; B is Fe. AB2O4 nanoparticles belong to the cubic system, and the space group is Specifically, the flexible magneto-optical composite material is Fe3O4-ZIF-8@PgC5Cu / PMMA or CoFe2O4-ZIF-8@PgC5Cu / PMMA or NiFe2O4-ZIF-8@PgC5Cu / PMMA; wherein Fe3O4 or CoFe2O4 or NiFe2O4 nanoparticles are uniformly dispersed in ZIF-8 with fixed pores, and the surface of ZIF-8 is modified with PgC5Cu as a bridging agent to make it uniformly dispersed in PMMA, thereby successfully constructing a flexible magneto-optical composite material.
[0007] A low-cost, easily moldable flexible magneto-optical composite material comprises the following specific steps: (1) Preparation of inorganic-organic nanocomposites: FeSO4·7H2O and (CH3COO)2Zn·2H2O (molar ratio of FeSO4·7H2O:(CH3COO)2Zn·2H2O not exceeding 0.43 / 0.55) were added with appropriate amount of deionized water and mixed evenly to prepare solution A; 2-methylimidazole C4H6N2 was added with appropriate amount of deionized water and mixed evenly to prepare solution B; solution B was quickly poured into solution A and stirred for 30 min, and then washed with water, methanol, and dichloromethane (DCM) three times each, and sealed with DCM. The sample Fe3O4-ZIF-8 was referred to as Fe-ZIF-8; (2) Preparation of raw materials CoFe2O4-ZIF-8 or NiFe2O4-ZIF-8: FeSO4·7H2O, Co(NO3)2·6H2O or Ni(NO3)2·6H2O, (CH3COO)2Zn·2H2O were added to deionized water and mixed evenly to prepare solution C; 2-methylimidazole was added to deionized water and mixed evenly to prepare solution D; solution D was quickly poured into solution C and stirred for 30 min, then transferred to a reactor containing a polytetrafluoroethylene liner, heated at 120°C for 2 h, cooled to room temperature, washed with water, methanol, and dichloromethane three times each, and sealed with dichloromethane. (3) Preparation of organic-inorganic polymer flexible magneto-optical composite materials: Weigh the two raw materials accurately according to the mass ratio of 1:20 between amylphthalene copper PgC5Cu and Fe3O4-ZIF-8 or CoFe2O4-ZIF-8 or NiFe2O4-ZIF-8, and place them in centrifuge tubes A and B respectively. Add dichloromethane (DCM) to centrifuge tube B at a mass ratio of 1:10 and mix them by ultrasonication. Add DCM to centrifuge tube A at a mass ratio of 1:5. After PgC5Cu is dissolved, add it to the sample in centrifuge tube B. After ultrasonic reaction for 3 min, centrifuge, wash with DCM 3 times, and seal the sample Fe3O4-ZIF-8@PgC5Cu or CoFe2O4-ZIF-8@PgC5Cu or NiFe2O4-ZIF-8@PgC5Cu with DCM. Then, according to the mass ratio of sample Fe3O4-ZIF-8@PgC5Cu or CoFe2O4-ZIF-8@PgC5Cu or NiFe2O4-ZIF-8@PgC5Cu to PMMA solution (0.003:1, 0.005:1, 0.01:1, 0.015:1), PgC5Cu modified AB2O4-ZIF-8 sealed in DCM was added to polymethyl methacrylate (PMMA) solution (dissolved in 1 g PMMA / 5 ml DCM), stirred evenly, and AB2O4-ZIF-8@PgC5Cu / PMMA flexible material dissolved in DCM solvent was prepared.
[0008] Furthermore, the reaction conditions in steps (1) and (2) are all synthesized at room temperature.
[0009] Furthermore, pentylphthalene copper PgC5Cu was synthesized according to the literature (Engineering Plasticization Resistant Gas Separation Membranes Using Metal-Organic Nanocapsules. DOI: 10.1039 / d0sc01498b).
[0010] Furthermore, the flexible material can be solidified and formed after the dichloromethane solvent evaporates. The flexible material can be used to prepare magneto-optical elements with special shapes according to the requirements of special-shaped magneto-optical devices.
[0011] Further, AB2O4-ZIF-8@PgC5Cu / PMMA, wherein A is Co, Ni; and B is Fe. The composite material is synthesized by accurately weighing FeSO4·7H2O, (CH3COO)2Zn·2H2O, Co(NO3)2·6H2O or Ni(NO3)2·6H2O (molar ratio of FeSO4·7H2O + Co(NO3)2·6H2O: (CH3COO)2Zn·2H2O not exceeding 0.43 / 0.55 or molar ratio of FeSO4·7H2O + Ni(NO3)2·6H2O: (CH3COO)2Zn·2H2O not exceeding 0.43 / 0.55) in a beaker, adding an appropriate amount of deionized water and mixing evenly to prepare solution A; accurately weighing C4H6N2 in a beaker according to the stoichiometric ratio, adding an appropriate amount of deionized water and mixing evenly to prepare solution B; quickly pouring solution B into solution A and stirring for 30 minutes, transferring to a polytetrafluoroethylene liner, and reacting in a reactor at 120° C. for 2 h later, the samples were washed three times with water, methanol, and dichloromethane (DCM) respectively, and then sealed with DCM; Furthermore, the composite material is expected to find practical applications in optical fiber communications, integrated optical devices, miniaturization, and novel special-shaped magneto-optical devices.
[0012] The present invention uses in-situ symbiosis technology to evenly disperse Fe3O4 or CoFe2O4 or NiFe2O4 nanoparticles with strong magneto-optical effect but easy to agglomerate in MOF (metal organic framework ZIF-8) with fixed pores, and uses PgC5Cu (a copper complex with a specific configuration, a bridging agent for ZIF-8 and PMMA) to modify the surface of ZIF-8 so that it is evenly dispersed in PMMA, and successfully constructs a composite material with excellent magneto-optical properties. This innovative design not only maintains the original structural stability and optical transparency of the material, but also gives it unprecedented flexibility and processability, making it possible to achieve lightweight, portable and flexible magneto-optical devices. Compared with traditional pure inorganic magneto-optical crystals, magneto-optical glass and other materials, the present invention has the advantages of simple preparation method, short production cycle, significantly reduced energy consumption and cost, easy molding and high flexibility, so that it can adapt to a wider range of application scenarios.
[0013] The significant advantages of the present invention are: (1) The flexible magneto-optical composite material AB2O4-ZIF-8@PgC5Cu / PMMA prepared by the present invention has an optical transmittance of up to 80% in the 800-1500 nm band.
[0014] (2) The flexible magneto-optical composite material AB2O4-ZIF-8@PgC5Cu / PMMA prepared by the present invention has low preparation cost and short cycle, and also exhibits excellent magnetic and optical properties, providing a high-performance, low-cost solution for the fields of magneto-optics, optical integration, etc.
[0015] (3) The flexible magneto-optical composite material AB2O4-ZIF-8@PgC5Cu / PMMA prepared by the present invention is unique in that the preparation process is simple and efficient. It can be directly formed after the solvent (DCM) evaporates naturally without any additional processing steps, showing excellent self-assembly performance and material molding convenience. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The powder X-ray diffraction (XRD) spectra of ZIF-8, Fe-ZIF-8 and Fe-ZIF-8@PgC5Cu are shown; Figure 2 Raman spectra of ZIF-8, Fe-ZIF-8, and Fe3O4 powders; Figure 3 xFe-ZIF-8@PgC5Cu / PMMA(x (Fe-ZIF-8@PgC5Cu: PMMA) =3, 5,10,15×10 -3 ) VSM spectrum of the film at room temperature; Figure 4 xFe-ZIF-8@PgC5Cu / PMMA(x(Fe-ZIF-8@PgC5Cu: PMMA) =3, 5,10,15×10 -3 ) film and the transmission spectra of pure PMMA film; Figure 5 xFe-ZIF-8@PgC5Cu / PMMA(x (Fe-ZIF-8@PgC5Cu: PMMA) =3, 5×10 -3 ) Specific Faraday rotation angle of the film at 1064 nm; Figure 6 xFe-ZIF-8@PgC5Cu / PMMA(x (Fe-ZIF-8@PgC5Cu: PMMA) =3, 5×10 -3 ) The specific Faraday rotation angle of the film at 1550 nm; Figure 7 The powder X-ray diffraction (XRD) spectra of NiFe2O4-ZIF-8 and CoFe2O4-ZIF-8; Figure 8 VSM spectra of Fe-ZIF-8, NiFe2O4-ZIF-8 and CoFe2O4-ZIF-8 powders before and after PgC5Cu modification at room temperature; Fig. 9 xNiFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3 )、xCoFe2O4-ZIF-8@PgC5Cu / PMMA(x is 5×10 -3 ) and the transmittance spectrum of PMMA film; Fig.10 xNiFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3 ) and xCoFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3 ) at 1064 nm and 1550 nm. DETAILED DESCRIPTION
[0017] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with the implementation methods of specific examples, but the present invention is not limited to the examples given here.
[0018] Implementation Case 1 A method for preparing a low-cost, easily moldable flexible magneto-optical composite material Fe-ZIF-8@PgC5Cu / PMMA, the specific steps are as follows: (1) Preparation of inorganic-organic nanocomposites: 0.43 mmol FeSO4·7H2O and 0.55 mmol (CH3COO)2Zn·2H2O were added to 5 mL of deionized water and mixed evenly to prepare solution A; 0.55 mmol 2-methylimidazole C4H6N2 was added to 10 mL of deionized water and mixed evenly to prepare solution B; solution B was quickly poured into solution A and stirred for 30 min, then washed three times with water, methanol, and dichloromethane (DCM) in sequence, and the Fe-ZIF-8 sample was sealed with DCM; (2) Preparation of organic-inorganic polymer flexible magneto-optical composite materials: Weigh the two raw materials accurately according to the mass ratio of 1:20 between pentylphthalene copper (PgC5Cu) and Fe-ZIF-8, and place them in centrifuge tubes A and B respectively. Add dichloromethane (DCM) to centrifuge tube B at a mass ratio of 1:10 and mix them ultrasonically. Add DCM to centrifuge tube A at a mass ratio of 1:5. After PgC5Cu is dissolved, add it to the sample in centrifuge tube B. After ultrasonic reaction for 3 min, centrifuge, wash with DCM 3 times, and seal the Fe-ZIF-8@PgC5Cu sample with DCM. Then, according to the mass ratio of sample to PMMA solution (0.003:1, 0.005:1, 0.01:1, 0.015:1), the PgC5Cu-modified Fe-ZIF-8 sealed in DCM was added to the polymethyl methacrylate (PMMA) solution (dissolved in 1 g PMMA / 5 ml DCM) and stirred evenly to prepare the Fe-ZIF-8@PgC5Cu / PMMA flexible material dissolved in DCM solvent.
[0019] The phases of Fe-ZIF-8 and Fe-ZIF-8@PgC5Cu were characterized by X-ray diffraction (XRD) spectra (see Figure 1 ) shows that the characteristic peaks of Fe-ZIF-8 and Fe-ZIF-8@PgC5Cu are consistent with those of ZIF-8, but the characteristic peaks of Fe3O4 are not obvious in the XRD spectra of Fe-ZIF-8 and Fe-ZIF-8@PgC5Cu, while the Raman spectra (see Figure 2 ) showed that Fe-ZIF-8 had obvious characteristic peaks of Fe3O4, indicating that the material Fe3O4 and ZIF-8 were successfully composited.
[0020] Figure 3 xFe-ZIF-8@PgC5Cu / PMMA(x (Fe-ZIF-8@PgC5Cu: PMMA) =3, 5,10,15×10 -3 ) film at room temperature, its magnetism increases with the increase of x. -3 When the magnetic field of the film is 0.08 emμ·g -1 .
[0021] Figure 4 xFe-ZIF-8@PgC5Cu / PMMA(x (Fe-ZIF-8@PgC5Cu: PMMA) =3, 5,10,15×10 -3 )The transmittance spectrum of the film has an optical transmittance of up to 80% in the 800~1500 nm band.
[0022] The xFe-ZIF-8@PgC5Cu / PMMA (x (Fe-ZIF-8@PgC5Cu: PMMA) =3, 5×10 -3 ) film at 1064 nm. The results are as follows Figure 5 The saturation applied magnetic field of the film is 300 mT, xFe-ZIF-8@PgC5Cu / PMMA(x (Fe-ZIF-8@PgC5Cu: PMMA) =5×10 -3 The specific Faraday rotation angle of the film is 14.08 deg·cm -1 , the specific Faraday rotation angle at 1550 nm is 4.62 deg·cm -1 The optimal value of x is 0.015:1.
[0023] Implementation Case 2 A method for preparing a low-cost, easily moldable flexible magneto-optical composite material CoFe2O4-ZIF-8@PgC5Cu / PMMA, the specific steps are as follows: (1) Preparation of inorganic-organic nanocomposites: Add 0.28 mmol FeSO4·7H2O, 0.14 mmol Co(NO3)2·6H2O, and 0.55 mmol (CH3COO)2Zn·2H2O into 5 mL of deionized water and mix well to prepare solution A. Add 0.55 mmol 2-methylimidazole C4H6N2 into 10 mL of deionized water and mix well to prepare solution B. Pour solution B into solution A quickly, stir for 30 min, and transfer to a reactor containing a polytetrafluoroethylene liner, heat at 120℃ for 2 h, cool to room temperature, wash with water, methanol, and dichloromethane three times each, and seal the sample CoFe2O4-ZIF-8 with dichloromethane.
[0024] (2) Preparation of organic-inorganic polymer flexible magneto-optical composite materials: Accurately weigh the two raw materials of pentylphthalene copper PgC5Cu and CoFe2O4-ZIF-8 in a mass ratio of 1:20, and place them in centrifuge tubes A and B respectively. Add dichloromethane (DCM) to centrifuge tube B in a mass ratio of 1:10 and mix them ultrasonically. Add DCM to centrifuge tube A in a mass ratio of 1:5. After PgC5Cu is dissolved, add it to the sample in centrifuge tube B. After ultrasonic reaction for 3 min, centrifuge, wash with DCM three times, and seal the sample CoFe2O4-ZIF-8@PgC5Cu with DCM. Then, the PgC5Cu-modified CoFe2O4-ZIF-8 sealed in DCM was added to the polymethyl methacrylate (PMMA) solution (dissolved in 1 g PMMA / 5 ml DCM) at a mass ratio of 0.005:1 between the sample and the PMMA solution, and stirred evenly to prepare the CoFe2O4-ZIF-8@PgC5Cu / PMMA flexible material dissolved in DCM solvent, which was then transferred to a 1 cm cuvette for Faraday rotation angle testing.
[0025] The phases of CoFe2O4-ZIF-8 and CoFe2O4-ZIF-8@PgC5Cu were characterized by X-ray diffraction (XRD) spectra (see Figure 7 ) showed that CoFe2O4-ZIF-8 and CoFe2O4-ZIF-8@PgC5Cu had characteristic peaks of ZIF-8 and CoFe2O4, indicating that the material CoFe2O4 and ZIF-8 were successfully composited.
[0026] Figure 8 VSM spectra of Fe-ZIF-8, NiFe2O4-ZIF-8 and CoFe2O4-ZIF-8 powders at room temperature. CoFe2O4-ZIF-8 has a stronger magnetic property than Fe-ZIF-8, and its saturation magnetization can reach 11.22 emμ·g -1 After PgC5Cu was used to modify CoFe2O4-ZIF-8, the saturation magnetization was enhanced to 14.53 emμ·g -1 .
[0027] Fig. 9 xNiFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3 )、xCoFe2O4-ZIF-8@PgC5Cu / PMMA(x is 5×10 -3 ) and PMMA thin film transmission spectra, xCoFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3 ) has an optical transmittance of up to 75% in the 800~1500 nm band.
[0028] Fig.10 xNiFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3 ) and xCoFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3 ) at 1064 nm and 1550 nm. xCoFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3 )The saturation applied magnetic field of the film is 300 mT, xCoFe2O4-ZIF-8@PgC5Cu / PMMA(x (Fe-ZIF-8@PgC5Cu: PMMA) =5×10 -3 The specific Faraday rotation angle of the film at 1064 nm is 15.03 deg·cm -1 , the specific Faraday rotation angle at 1550 nm is 5.17 deg·cm -1 .
[0029] Implementation Case 3 A method for preparing a low-cost, easily moldable, flexible magneto-optical composite material NiFe2O4-ZIF-8@PgC5Cu / PMMA, Ni, the specific steps are as follows: (1) Preparation of inorganic-organic nanocomposites: Add 0.28 mmol FeSO4·7H2O, 0.14 mmol Ni(NO3)2·6H2O, and 0.55 mmol (CH3COO)2Zn·2H2O into 5 mL of deionized water and mix well to prepare solution A. Add 0.55 mmol 2-methylimidazole C4H6N2 into 10 mL of deionized water and mix well to prepare solution B. Pour solution B into solution A quickly, stir for 30 min, and transfer to a reactor containing a polytetrafluoroethylene liner, heat at 120℃ for 2 h, cool to room temperature, wash with water, methanol, and dichloromethane three times each, and seal the sample NiFe2O4-ZIF-8 with dichloromethane.
[0030] (2) Preparation of organic-inorganic polymer flexible magneto-optical composite materials: Weigh the two raw materials accurately according to the mass ratio of 1:20 between pentylphthalene copper (PgC5Cu) and NiFe2O4-ZIF-8, and place them in centrifuge tubes A and B respectively. Add dichloromethane (DCM) to centrifuge tube B at a mass ratio of 1:10 and mix them by ultrasonication. Add DCM to centrifuge tube A at a mass ratio of 1:5. After PgC5Cu is dissolved, add it to the sample in centrifuge tube B. After ultrasonic reaction for 3 min, centrifuge, wash with DCM 3 times, and seal the NiFe2O4-ZIF-8@PgC5Cu sample with DCM. Then, PgC5Cu-modified NiFe2O4-ZIF-8 sealed in DCM was added to a polymethyl methacrylate (PMMA) solution (dissolved in 1 g PMMA / 5 ml DCM) at a mass ratio of 0.005:1 between the sample and the PMMA solution, and stirred evenly to prepare a NiFe2O4-ZIF-8@PgC5Cu / PMMA flexible material dissolved in DCM solvent, which was then transferred to a 1 cm cuvette for Faraday rotation angle testing.
[0031] The phases of NiFe2O4-ZIF-8 and NiFe2O4-ZIF-8@PgC5Cu were characterized by X-ray diffraction (XRD) spectra (see Figure 7 ) showed that NiFe2O4-ZIF-8 and NiFe2O4-ZIF-8@PgC5Cu had characteristic peaks of ZIF-8 and NiFe2O4, indicating that the material NiFe2O4 was successfully composited with ZIF-8.
[0032] Figure 8 VSM spectra of Fe-ZIF-8, NiFe2O4-ZIF-8 and CoFe2O4-ZIF-8 powders before and after PgC5Cu modification at room temperature. Compared with Fe-ZIF-8 and CoFe2O4-ZIF-8, NiFe2O4-ZIF-8 has the largest magnetic properties, with a saturation magnetization of 17.51 emμ·g -1 The magnetic properties of NiFe2O4-ZIF-8@PgC5Cu are 16.24 emμ·g -1 .
[0033] Fig. 9 xNiFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3 )、xCoFe2O4-ZIF-8@PgC5Cu / PMMA(x is 5×10 -3 ) and PMMA thin film transmission spectra, xNiFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3) The film has an optical transmittance of up to 78% in the 800~1500 nm band.
[0034] Fig.10 xNiFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3 ) and xCoFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3 ) at 1064 nm and 1550 nm. xNiFe2O4-ZIF-8@PgC5Cu / PMMA (x is 5×10 -3 ) film under saturated external magnetic field of 300 mT, xNiFe2O4-ZIF-8@PgC5Cu / PMMA(x (Fe-ZIF-8@PgC5Cu: PMMA) =5×10 -3 The specific Faraday rotation angle of the film at 1064 nm is 16.93 deg·cm -1 , the Faraday rotation angle at 1550 nm is 5.70 deg·cm -1 .
[0035] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A low-cost, easily moldable flexible magneto-optical composite material, characterized in that: The composite material is Fe3O4-ZIF-8@PgC5Cu / PMMA or CoFe2O4-ZIF-8@PgC5Cu / PMMA or NiFe2O4-ZIF-8@PgC5Cu / PMMA; among them, Fe3O4 or CoFe2O4 or NiFe2O4 nanoparticles are uniformly dispersed in ZIF-8 with fixed pores, and the surface of ZIF-8 is modified with PgC5Cu as a bridging agent to make it uniformly dispersed in PMMA, and a flexible magneto-optical composite material is successfully constructed.
2. A method for preparing the low-cost, easily moldable flexible magneto-optical composite material as claimed in claim 1, characterized in that: The following steps are involved: (1) Preparation of raw material Fe3O4-ZIF-8: Add FeSO4·7H2O and (CH3COO)2Zn·2H2O to deionized water and mix well to prepare solution A; add 2-methylimidazole to deionized water and mix well to prepare solution B; quickly pour solution B into solution A and stir for 30 min, then wash with water, methanol and dichloromethane three times respectively, and seal the sample Fe3O4-ZIF-8 with dichloromethane; (2) Preparation of raw materials CoFe2O4-ZIF-8 or NiFe2O4-ZIF-8: Add FeSO4·7H2O, Co(NO3)2·6H2O or Ni(NO3)2·6H2O, (CH3COO)2Zn·2H2O to deionized water and mix well to prepare solution C; add 2-methylimidazole to deionized water and mix well to prepare solution D; quickly pour solution D into solution C, stir for 30 min, transfer to a reactor with a polytetrafluoroethylene liner, heat at 120℃ for 2 h, cool to room temperature, wash with water, methanol, and dichloromethane three times each, and seal the sample CoFe2O4-ZIF-8 or NiFe2O4-ZIF-8 with dichloromethane; (3) Preparation of organic-inorganic polymer flexible magneto-optical composite materials: Weigh the two raw materials accurately according to the mass ratio of pentylphthalene copper PgC5Cu to Fe3O4-ZIF-8 or CoFe2O4-ZIF-8 or NiFe2O4-ZIF-8 of 1:20, and place them in centrifuge tubes respectively. Add dichloromethane and mix them by ultrasonic. After PgC5Cu is dissolved, add the dichloromethane dispersion of Fe3O4-ZIF-8 or CoFe2O4-ZIF-8 or NiFe2O4-ZIF-8 and mix them by ultrasonic. min later, centrifuged, washed with dichloromethane three times, and then sealed with dichloromethane. Then, the samples Fe3O4-ZIF-8@PgC5Cu or CoFe2O4-ZIF-8@PgC5Cu or NiFe2O4-ZIF-8@PgC5Cu were added to the PMMA solution and stirred evenly to prepare Fe3O4-ZIF-8@PgC5Cu / PMMA or CoFe2O4-ZIF-8@PgC5Cu / PMMA or NiFe2O4-ZIF-8@PgC5Cu / PMMA flexible magneto-optical composite materials dissolved in dichloromethane solvent.
3. The preparation method according to claim 2, characterized in that: In step (1), the molar ratio of FeSO4·7H2O:(CH3COO)2Zn·2H2O does not exceed 0.43 / 0.
55.
4. The preparation method according to claim 2, characterized in that In step (2), the PMMA solution is prepared by dissolving 1 g PMMA in 5 ml dichloromethane.
5. The preparation method according to claim 2, characterized in that: In step (3), the mass ratio of Fe3O4-ZIF-8@PgC5Cu or CoFe2O4-ZIF-8@PgC5Cu or NiFe2O4-ZIF-8@PgC5Cu to PMMA solution is 0.003-0.015:
1.
6. The preparation method according to claim 2, characterized in that: After the dichloromethane solvent evaporates, the flexible magneto-optical composite material can be solidified into shape.
7. The preparation method according to claim 2, characterized in that: The flexible magneto-optical composite material can be used to prepare magneto-optical elements with special shapes according to the requirements of special-shaped magneto-optical devices.
8. A use of the low-cost, easily moldable flexible magneto-optical composite material as claimed in claim 1 in the preparation of magneto-optical devices, characterized in that: The magneto-optical device includes a magneto-optical isolator, a miniaturized or integrated optical integrated device, an optical circulator or a magneto-optical modulator.
Citation Information
Patent Citations
Polymer-based flexible composite material having both ferroelectric properties and ferromagnetic properties, and preparation method thereof
CN105949683A
Preparation method of core-shell type metal organic framework heterogeneous composite material
CN107497495A
Method for synthesizing hollow core-shell magnetic metal-organic framework composite material
CN107876014A
Preparation method and application of positive ion post-modification magnetic metal organic framework composite material
CN108970585A
Single-particle-layer metal organic framework mixed matrix nano-porous membrane and preparation method thereof
CN116328559A
Cited By
Low-cost and easy-to-form silicon-based epitaxial magneto-optical film as well as preparation method and application thereof
CN119902389A
A low-cost, easily formed silicon-based epitaxial magneto-optical thin film, its preparation method, and its application.
CN119902389B